2023
DOI: 10.1038/s41586-023-06197-z
|View full text |Cite
|
Sign up to set email alerts
|

A tripartite rheostat controls self-regulated host plant resistance to insects

Abstract: Plants deploy receptor-like kinases and nucleotide-binding leucine-rich repeat receptors to confer host plant resistance (HPR) to herbivores1. These gene-for-gene interactions between insects and their hosts have been proposed for more than 50 years2. However, the molecular and cellular mechanisms that underlie HPR have been elusive, as the identity and sensing mechanisms of insect avirulence effectors have remained unknown. Here we identify an insect salivary protein perceived by a plant immune receptor. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 63 publications
0
19
0
3
Order By: Relevance
“…Pathogen/insect-derived effectors can be powerful molecular probes to discovering novel plant regulators/responses to biotic attacks. Although other piercing/sucking herbivores derived effectors, such as Btfer1, LsPDI1, LsSP1, Mp55, DNase II and BISP, have been reported as defense-suppressive effectors, 33-38 our discovery of intracellular acidification as a plant defense response and our finding that brown planthopper (BPH) secretes NICA as a counter-defense measure illustrates host cell pH homeostasis as a novel battlefield that has not been revealed in any plant-biotic interactions.…”
Section: Discussionmentioning
confidence: 84%
“…Pathogen/insect-derived effectors can be powerful molecular probes to discovering novel plant regulators/responses to biotic attacks. Although other piercing/sucking herbivores derived effectors, such as Btfer1, LsPDI1, LsSP1, Mp55, DNase II and BISP, have been reported as defense-suppressive effectors, 33-38 our discovery of intracellular acidification as a plant defense response and our finding that brown planthopper (BPH) secretes NICA as a counter-defense measure illustrates host cell pH homeostasis as a novel battlefield that has not been revealed in any plant-biotic interactions.…”
Section: Discussionmentioning
confidence: 84%
“…Further research has revealed that the carboxyl terminal of NlMLP regulates Ca 2+ flux and the JA signaling pathway, activating the expression of defense-related genes and inducing callose deposition [95]. Guo et al (2023) identified and characterized the first insect salivary protein perceived by the plant immune receptor, which is a saliva protein BISP (BPH14interacting salivary protein) of the brown planthopper (BPH) [96]. In susceptible varieties, [92], and complementing and perfecting the molecular network mechanism related to all BPH-resistant genes].…”
Section: Recognition Of Feeding Signals Of Rice To Bphmentioning
confidence: 99%
“…In susceptible varieties, BISP targets OsRLCK185 and inhibits the basic defense. In varieties carrying the brown planthopper resistance gene Bph14, Bph14 binds to BISP and activates the host immune response but inhibits rice growth [96]. BISP-Bph14 binds to the selective autophagic cargo receptor OsNBR1 and results in the degradation of BISP through the autophagic pathway, downregulating rice resistance against BPH and restoring the plant growth [96].…”
Section: Recognition Of Feeding Signals Of Rice To Bphmentioning
confidence: 99%
See 1 more Smart Citation
“…BPH14互作. 该蛋白命名为BPH14-Interacting Salivary Protein (BISP) [9] . BISP在褐飞虱唾液腺中高表达, 在褐飞虱取食时被 图 1 (网络版彩色)BISP诱导的免疫调节模型 [9] .…”
Section: 为了进一步深入揭示水稻抗褐飞虱机理 我们采用酵母unclassified